La protection et la valorisation juridique de la biodiversité de la Caraïbe et des Guyanes : propriété intellectuelle et dispositif APA - Céline Castets-Renard (VertigO, 2012)
This article’s aim is to show the main conditions to encourage the emerging of a market on genetic ressources in Caraïbe and Guyane, with a view to the valorisation and the protection of the biodiversity, in compliance with the Rio Convention on biodiversity (1992).